2019
DOI: 10.21608/aadj.2019.60188
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of The Effect of Demineralized Bone Matrix with and Without Low Level Laser Therapy on The Treatment of Periodontal Infra-Bony Defects (Randomized Clinical Trial)

Abstract: Objective: This study aimed at comparing clinically and radiographically the therapeutic effect of low level laser therapy and demineralized bone matrix, used in management of periodontal intrabony defect. Subjects and methods: Thirty two non-smoking patients aged between 28-51 years with severe chronic periodontitis participated in this randomized clinical study. Patients were randomly assigned into one of 2 groups (16 patients each): demineralized bone grafting alone of the intrabony defect, control group (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, the differences were statistically insignificant between the two experimental sites. Gamil et al 27 observed similar results in the management of intrabony defects where the defect depth was reduced from 5.4 ± 0.7 mm to 0.9 ± 0.5 mm at six months postoperatively in defects treated with LLLT and demineralized bone matrix than defects treated with demineralized bone matrix alone with a mean difference of 2.0 ± 0.4 mm, respectively. The results of the present study were similar to the study by Vaid et al, 25 where the defect area was reduced from 10.55 mm to 6.35 mm at six months postoperatively in the CGF group.Thalaimalai et al 28 also observed 2.44 mm of radiographic bone fill in patients treated with simplified papilla preservation flap (SPPF) with LLLT + PRF than patients treated with SPPF + PRF alone at the end of six months, similar to the present study in the treatment of intrabony periodontal defects.…”
Section: Discussionmentioning
confidence: 73%
“…However, the differences were statistically insignificant between the two experimental sites. Gamil et al 27 observed similar results in the management of intrabony defects where the defect depth was reduced from 5.4 ± 0.7 mm to 0.9 ± 0.5 mm at six months postoperatively in defects treated with LLLT and demineralized bone matrix than defects treated with demineralized bone matrix alone with a mean difference of 2.0 ± 0.4 mm, respectively. The results of the present study were similar to the study by Vaid et al, 25 where the defect area was reduced from 10.55 mm to 6.35 mm at six months postoperatively in the CGF group.Thalaimalai et al 28 also observed 2.44 mm of radiographic bone fill in patients treated with simplified papilla preservation flap (SPPF) with LLLT + PRF than patients treated with SPPF + PRF alone at the end of six months, similar to the present study in the treatment of intrabony periodontal defects.…”
Section: Discussionmentioning
confidence: 73%